2005
DOI: 10.2337/diabetes.54.5.1385
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Protein 1 Is Necessary for Norepinephrine-Induced Glucose Utilization in Brown Adipose Tissue

Abstract: Sympathetic stimulation activates glucose utilization in parallel with fatty acid oxidation and thermogenesis in brown adipose tissue (BAT) through the beta-adrenergic receptors. To clarify the roles of the principal thermogenic molecule mitochondrial uncoupling protein 1 (UCP1) in the sympathetically stimulated glucose utilization, we investigated the uptake of 2-deoxyglucose (2-DG) into BAT and some other tissues of UCP1-knockout (KO) mice in vivo. In wild-type (WT) mice, administration of norepinephrine (NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
144
5
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(159 citation statements)
references
References 36 publications
9
144
5
1
Order By: Relevance
“…However, our results indicate that β-adrenoceptors activate AMPK independently of activation of UCP1 (but that there is a basal difference between cells isolated from Ucp1 +/+ and Ucp1 −/− animals that we are currently unable to explain but is clearly independent of UCP1 production). The differences between the results of Inokuma et al [48] and the present results are most likely to be a consequence of the different systems used. Cells in culture have not previously been exposed to a sympathetic stimulus, whereas this is probably the case in intact mice at 26°C.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, our results indicate that β-adrenoceptors activate AMPK independently of activation of UCP1 (but that there is a basal difference between cells isolated from Ucp1 +/+ and Ucp1 −/− animals that we are currently unable to explain but is clearly independent of UCP1 production). The differences between the results of Inokuma et al [48] and the present results are most likely to be a consequence of the different systems used. Cells in culture have not previously been exposed to a sympathetic stimulus, whereas this is probably the case in intact mice at 26°C.…”
Section: Discussioncontrasting
confidence: 57%
“…It was recently suggested that sympathetically stimulated glucose utilisation in brown adipose tissue is due to the serial activation of UCP1 and AMPK [48]. However, our results indicate that β-adrenoceptors activate AMPK independently of activation of UCP1 (but that there is a basal difference between cells isolated from Ucp1 +/+ and Ucp1 −/− animals that we are currently unable to explain but is clearly independent of UCP1 production).…”
Section: Discussioncontrasting
confidence: 55%
“…As a consequence, the fatty acid composition of BAT triglycerides alters rapidly to closely reflect the composition of dietary lipids (12) indicative of rapid cellular uptake of serum FFAs. While mechanisms underlying enhanced glucose uptake by BAT following adrenergic stimulation have been studied intensely in the past (13)(14)(15), little is known regarding protein-mediated fatty acid uptake by this tissue.…”
mentioning
confidence: 99%
“…On the other hand, acute blockage of a-adrenergic signaling resulted in stimulation of AMPK activity, mediated by alteration in AMPK a Thr 172 phosphorylation, which could be secondary to diminished oxygen consumption in BAT (Pulinilkunnil et al 2011). Acute stimulation of b-adrenergic signaling in mice also resulted in increased AMPK activity in BAT, leading to increased glucose uptake with both effects abolished in UCP1 knock-out mice (Inokuma et al 2005). In brown adipocytes differentiated in vitro, b-adrenergic stimulation was also found to increase AMPK phosphorylation and b-adrenergically mediated glucose uptake required AMPK.…”
Section: Ampk Function In Adipose Tissuementioning
confidence: 99%